Digital Native Teachers: A Study on the Impact of TikTok Microlearning Content in Pedagogical Practices Among Pre-service Educators - Ode Abdurrachman; Tazkiyah Navysah Ar Rachmah (PT. Sinergi Bersahaja Sejahtera, 2025)
Background. The rapid growth of short-form video platforms such as TikTok has transformed the way knowledge is created, shared, and consumed. For digital native teachers—those who have grown up in the digital era—TikTok represents not only a form of entertainment but also an emerging pedagogical tool. Microlearning content delivered through TikTok’s concise and visually engaging format has the potential to enhance pre-service educators’ pedagogical knowledge, creativity, and technological competence. Purpose. This quantitative study aimed to examine the impact of TikTok-based microlearning content on the pedagogical practices of pre-service educators. Specifically, it investigated how exposure to and engagement with TikTok microlearning videos influence teaching creativity, digital literacy, and classroom innovation. Method. A total of 210 pre-service educators from three Indonesian universities participated in this study. Data were collected using an online questionnaire measuring perceived usefulness, engagement level, pedagogical innovation, and digital self-efficacy. Statistical analyses, including correlation and multiple regression tests, were conducted to determine the relationships between exposure to TikTok microlearning and pedagogical outcomes. Results. The findings revealed that pre-service educators with higher engagement in TikTok microlearning content demonstrated significantly greater levels of pedagogical innovation and digital teaching readiness. The regression analysis indicated that engagement frequency and perceived usefulness were the strongest predictors of pedagogical creativity. Conclusion. This study underscores the transformative potential of TikTok microlearning in shaping the pedagogical practices of digital native teachers. Integrating short-form educational content into teacher education programs can foster creativity, digital competence, and reflective teaching habits.